Self-Reported Measures of Discretionary Salt Use Accurately Estimated Sodium Intake Overall but not in Certain Subgroups of US Adults from 3 Geographic Regions in the Salt Sources Study - Quader, Zerleen S (J Nutr, 2019)
BACKGROUND: Excess sodium intake can increase blood pressure, and high blood pressure is a major risk factor for cardiovascular disease. Accurate population sodium intake estimates are essential for monitoring progress toward reduction, but data are limited on the amount of sodium consumed from discretionary salt. OBJECTIVES: The aim of this study was to compare measured sodium intake from salt added at the table with that estimated according to the Healthy People 2020 (HP 2020) methodology. METHODS: Data were analyzed from the 2014 Salt Sources Study, a cross-sectional convenience sample of 450 white, black, Asian, and Hispanic adults living in Alabama, Minnesota, and California. Sodium intake from foods and beverages was assessed for each participant through the use of 24-h dietary recalls. Estimated sodium intake from salt used at the table was assessed from self-reported frequency and estimated amounts from a previous study (HP 2020 methodology). Measured intake was assessed through the use of duplicate salt samples collected on recall days. RESULTS: Among all study participants, estimated and measured mean sodium intakes from salt added at the table were similar, with a nonsignificant difference of 8.9 mg/d (95% CI: −36.6, 54.4 mg/d). Among participants who were non-Hispanic Asian, Hispanic, had a bachelor's degree or higher education, lived in California or Minnesota, did not report hypertension, or had normal BMI, estimated mean sodium intake was 77–153 mg/d greater than measured intake (P < 0.05). The estimated mean sodium intake was 186–300 mg/d lower than measured intake among participants who were non-Hispanic black, had a high school degree or less, or reported hypertension (P < 0.05). CONCLUSIONS: The HP 2020 methodology for estimating sodium consumed from salt added at the table may be appropriate for the general US adult population; however, it underestimates intake in certain population subgroups, particularly non-Hispanic black, those with a high school degree or less, or those with self-reported hypertension. This study was registered at clinicaltrials.gov as NCT02474693.